Perfecting Your Spread Plate Technique - Diane Hartman (American Society for Microbiology, 2011)
The Spread Plate Technique, in conjunction with serial dilutions, is a valuable research tool. In this example, dye is used to accentuate the visible volume of each aliquot and the dispersion pattern on the agar. With the utilization of a second dye, each agar plate can be used twice. The immediate feedback and personal evaluation of these techniques provide an active learning experience that students remember.